2011
DOI: 10.1007/s00264-010-1204-4
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of wire cerclage stabilisation of the medial hinge in intramedullary nailing for the treatment of subtrochanteric femoral fractures: a biomechanical study

Abstract: Purpose Reduction and intramedullary fixation of subtrochanteric fractures is often challenging. Osteosynthesis frequently fails and a higher rate of non-unions is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 22 publications
6
35
0
1
Order By: Relevance
“…Besides the use of fracture table, indirect reduction of the fracture can be achieved with the supplement of circumferential wire. 19,20 Unlike cephalomedullary nail, PF-LCP allows circumferential wire without additional incision. Cerclage wiring is an alternative technique to achieve reduction in difficult fractures 21,22 From recent cadaveric study, cerclage wiring resulted in only minimal disruption of femoral blood supply 23 .…”
Section: In Ordermentioning
confidence: 99%
“…Besides the use of fracture table, indirect reduction of the fracture can be achieved with the supplement of circumferential wire. 19,20 Unlike cephalomedullary nail, PF-LCP allows circumferential wire without additional incision. Cerclage wiring is an alternative technique to achieve reduction in difficult fractures 21,22 From recent cadaveric study, cerclage wiring resulted in only minimal disruption of femoral blood supply 23 .…”
Section: In Ordermentioning
confidence: 99%
“…In his study all fractures healed and there was no implant-related complications. In an experimental study, Gontze et al [10] compared the laudability of osteosynthesis of unstable per and subtrochanteric fractures and found that the PFN could bear the highest loads of all devices. Simmermacher et al [11] in a clinical multicenter study with 191 subtrochanteric fractures treated with PFN reported technical failures of the PFN after poor reduction, malrotation or wrong choice of screws in 5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, I have read the article "The benefit of wire cerclage stabilisation of the medial hinge in intramedullary nailing for the treatment of subtrochanteric femoral fractures: a biomechanical study" with the great interest [1]. In their article, the authors argue that osteosynthesis frequently fails and a higher rate of nonunion is found in the subtrochanteric region of the femur.…”
mentioning
confidence: 99%
“…In their article, the authors argue that osteosynthesis frequently fails and a higher rate of nonunion is found in the subtrochanteric region of the femur. As I understand from their article, this nonunion is due to fracture distraction (commonly seen after intramedullary nailing) in the subtrochanteric region, and they believe that supporting the medial column with cerclage wiring can resolve this problem [1]. They concluded that "a mini-open approach to difficult fractures could be helpful in reducing the fracture with a clamp and is sometimes essential.…”
mentioning
confidence: 99%
See 1 more Smart Citation